The DNA barcode of red fruit pandan (Pandanaceae) cultivar from Wamena, Papua Province, Indonesia based on matK gene - LISYE IRIANA ZEBUA; TRI GUNAEDI; I MADE BUDI; NELLY LUNGA (Society for Indonesian Biodiversity, 2019)
Abstract. Zebua LI, Gunaedi T, Budi IM, Lunga N. 2019. The DNA barcode of red fruit pandan (Pandanaceae) cultivar from Wamena, Papua Province, Indonesia based on matK gene. Biodiversitas 20: 3405-3412. The red fruit pandan has been used by the people of Wamena in central highlands of Papua as medicinal plants, food ingredients, and religious ceremonies. Based on morphological characters, there are 39 cultivars of red fruit pandan in New Guinea. A standard method for plant species identification through DNA barcodes has been recommended to use matK gene. The research aimed to determine similarities in DNA barcode sequences of six red fruit pandan cultivars with its close relative that listed in NCBI system and to recommend the reliable DNA barcode for identification of this cultivar. Polymerase Chain Reaction was employed DNA to amplify matK gene fragments using an available forward primer (5’CGA TCT ATT CAT TCA ATA TTT C 3’) and reverse primer (5’TCT AGC ACA CGA AAGTCG AAG T 3’). The software BLAST, Bioedit, and ClustalX were used to analyze the data. Barcode DNA of red fruit pandan showed 1474 bp nucleotides sequence based on matK gene. An indication of six red fruit pandan cultivars showed that high similarity 99% with Pandanus conoideus Lam. It can be concluded that matK gene can be used to determine the species level in Pandanus.